The Current Status of Indigenous Freshwater Fishes in Jordan (Bangladesh Journal of Zoology, 2012)
Considerable changes were revealed in the indigenous freshwater fish fauna during a field survey of six years from 2006 to 2008. Most of them are endangered and one endemic species, Aphanius sirhani, is under the threat of extinction. Four other species, Garra rufa, G. ghorensis, Nemacheilus insignis and  Aphanius dispar richardsoni are also endangered. Misuse of the limited water resources, intensification of agriculture, overexploitation of fishing and the  introduction of exotic species are considered to be major threats to Jordans  freshwater fish fauna. DOI: http://dx.doi.org/10.3329/bjz.v40i1.12895 Bangladesh J. Zool. 40(1): 59-67, 2012